The Dilemma of Illegal Indonesian Migrant Workers : Between Rural Unemployment Solutions and Weak Protection - Yougie Alhabsy Barnadi; Eny Haryati; Dian Ferriswara (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2025)
This study aims to describe and analyze: positive impacts with negative impacts as a result of Illegal Indonesian Migrant Workers and How Legal Protection in Indonesian Migrant Workers Ilega. The research is a qualitative descriptive analysis. The data analysis technique uses the technique developed by McNabb (2002), namely Grouping the data according to key constructs, Identifying bases for interpretation, Developing generalizations from the data, Testing Alternative interpretations and Forming and/or refining generalizable theory from case study. The results show that the current migration process, due to its intense dynamics, has a strong social and economic impact. The impact affects almost all sectors of society. In addition, it has an impact on the sending and receiving countries, especially its human resources. Positive and negative impacts of international labor migration on human capital in sending and receiving countries. Legal protection for Indonesian Migrant Workers has been comprehensively regulated through various laws and regulations, with the aim of providing maximum protection from various aspects. The state ensures protection for Indonesian Migrant Workers in three main stages: before work, during work, and after work. This protection includes administrative, technical, social security, security, as well as complaint assistance and management of work results after returning to Indonesia. The Indonesian Migrant Workers Protection Agency (BP2MI) is a non-ministerial body formed based on Law Number 18 of 2017 and Presidential Regulation Number 90 of 2019 to provide integrated services and protection for Indonesian Migrant Workers. BP2MI has various authorities, including the implementation of policies, services, social security supervision, issuance of recruitment permits, document verification, and coordination of protection during employment. BP2MI is also tasked with managing facilities, rehabilitation, reintegration, and social and economic empowerment for Indonesian Migrant Workers and their families. BP2MI collaborates with various stakeholders from the central government to villages to ensure optimal services and protection for Indonesian Migrant Workers.